Effect Pengaruh Brisk Walking Exercise Terhadap Glukosa Darah Pada Pasien Diabetes Melitus Tipe 2 - Martini, Ni Ketut Sri; Prihandini, Cludia Wuri; putra, Putu wira kusuma (2024)
Patients with type 2 diabetes mellitus often have problems with blood glucose instability. One of the treatments to stabilize blood sugar is physical exercise, namely brisk walking exercise. This study aims to determine the effect of brisk walking exercise on blood glucose in patients with type 2 diabetes mellitus at UPTD Puskesmas Mengwi III. The study was conducted with a pre-experimental design with a pre-test and post-test one group design which was carried out from March to April 2024 with a total sample of 15 respondents selected by purposive sampling technique. Data were collected using a glucometer. Data were analyzed using the Paired T Test. The results showed that blood glucose in patients with diabetes mellitus before being given brisk walking exercise with an average of 143.4 mg/dl and a decrease in blood glucose after being given brisk walking exercise with an average of 127 mg/dl. Analysis of the effect of brisk walking exercise on blood glucose in patients with type 2 diabetes mellitus obtained a p value <0.001, so it can be said that there is an effect of brisk walking exercise on blood glucose in patients with type 2 diabetes mellitus at UPTD Puskesmas Mengwi III. The recommendations of this study are expected to be input for nurses to provide complementary therapy, namely brisk walking exercise in lowering blood pressure